L-cysteine methyl ester overcomes the deleterious effects of morphine on ventilatory parameters and arterial blood-gas chemistry in unanesthetized rats - Getsy, Paulina M.; Baby, Santhosh M.; May, Walter J.; Bates, James N.; Ellis, Christopher R.; Feasel, Michael G.; Wilson, Christopher G.; Lewis, Tristan H. J.; Gaston, Benjamin; Hsieh, Yee-Hsee; Lewis, Stephen J. (Frontiers in Pharmacology, 2022)
We are developing a series of thiolesters that produce an immediate and sustained reversal of the deleterious effects of opioids, such as morphine and fentanyl, on ventilation without diminishing the antinociceptive effects of these opioids. We report here the effects of systemic injections of L-cysteine methyl ester (L-CYSme) on morphine-induced changes in ventilatory parameters, arterial-blood gas (ABG) chemistry (pH, pCO2, pO2, sO2), Alveolar-arterial (A-a) gradient (i.e., the index of alveolar gas-exchange within the lungs) and antinociception in unanesthetized Sprague Dawley rats. The administration of morphine (10 mg/kg, IV) produced a series of deleterious effects on ventilatory parameters, including sustained decreases in tidal volume, minute ventilation, inspiratory drive and peak inspiratory flow that were accompanied by a sustained increase in end inspiratory pause. The administration of L-CYSme (500 mol/kg, IV) produced a rapid and long-lasting reversal of the deleterious effects of morphine on ventilatory parameters and a second injection of L-CYSme (500 mol/kg, IV) elicited pronounced increases in parameters, such as minute ventilation, to values well above pre-morphine levels. L-CYSme (250 or 500 mol/kg, IV) also produced an immediate and sustained reversal of the deleterious effects of morphine (10 mg/kg, IV) on arterial blood pH, pCO2, pO2, sO2 and A-a gradient, whereas L-cysteine (500 mol/kg, IV) itself was inactive. L-CYSme (500 mol/kg, IV) did not appear to modulate the sedative effects of morphine as measured by righting reflex times, but did diminish the duration, however, not the magnitude of the antinociceptive actions of morphine (5 or 10 mg/kg, IV) as determined in tail-flick latency and hindpaw-withdrawal latency assays. These findings provide evidence that L-CYSme can powerfully overcome the deleterious effects of morphine on breathing and gas-exchange in Sprague Dawley rats while not affecting the sedative or early stage antinociceptive effects of the opioid. The mechanisms by which L-CYSme interferes with the OR-induced signaling pathways that mediate the deleterious effects of morphine on ventilatory performance and by which L-CYSme diminishes the late stage antinociceptive action of the opioid remain to be determined.